PLCγ2 controls neutrophil-like cell sensitivity through calcium oscillation and gates chemoattractant concentration range for chemotaxis - Xu, Xuehua; Kim, Woo Sung; Lee, Arthur; Jin, Tian (Frontiers in Immunology, 2025)
The relationship between calcium oscillation and cell sensitivity is poorly understood. Calcium oscillation can occur spontaneously or be triggered upon receptor-ligand binding. The cytosolic [Ca2+] increase during calcium oscillation is initiated from Ca2+ release from the intracellular stores through the phospholipase C (PLC)-derived inositol 1,4,5-trisphosphate (IP3). Here, we show that neutrophil-like HL60 cells lacking PLCγ2 (plcg2kd) exhibit impaired spontaneous calcium oscillation and a diminished calcium response to chemoattractant stimulation. These defects result in reduced membrane targeting of RasGAP CAPRI (calcium-promoted Ras inactivator), and subsequent elevated Ras activations and enhanced downstream signaling, including PI3Kγ activation and actin polymerization. Notably, plcg2kd cells display increased sensitivity and can respond to chemoattractant gradients at a subsensitive concentrations. Taken together, our findings identify PLCγ2 as a key regulator of spontaneous and chemoattractant-induced calcium signaling and demonstrate its essential role in controlling cell sensitivity and chemoattractant concentration range for chemotaxis through CAPRI-dependent Ras signaling.